A New Topology of a Single-Phase Five-Level Inverter - Leonardus Heru Pratomo (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2020)
The power inverter technology with low harmonics content is used for many applications, such as in new and renewable energy sector. In the last decades, some researchers explored its inverter to minimize the harmonics content, and one of the solutions is a five-level inverter. A single-phase five-level inverter has a good performance in power conversion and improved performance. Nevertheless, the conventional five-level inverter topology always deals with many power semiconductor switches and a complex control algorithm. This paper, therefore, presents a new topology of a five-level inverter using four active switches.The new topology can work well as a single phase-five-level inverter with a novel Sinusoidal Pulse Width Modulation (SPWM) control algorithm using level-phase shifted carrier strategy. The new inverter has a simple power circuit and control strategy. The verification of this research is a simulation and prototype implementation, carried out in a laboratory. The results show that the proposed control strategy is capable of achieving five-level with a simple control strategy.